Effect of an adapted Taekwondo-based intervention on functional and motor abilities in elderly care home residents: a study protocol - Giuseppe Barone; Lorenzo Romano; Erika Pinelli; Laura Bragonzoni; Maria Scoppolini Massini; Raffaele Zinno; Giulio Senesi; Angelo Davalli (BMJ Open Sport & Exercise Medicine)
This pilot protocol study aims to evaluate the effects of an adapted Taekwondo-based intervention on upper limb strength and overall functional capacity in elderly care home residents. Considering the global trend of population ageing, physical activity interventions in care facilities are essential to mitigate functional decline and enhance well-being among this population. 20 participants will be stratified into walking and non-walking groups to reflect the diverse functional levels within the facility. The primary outcome will focus on upper limb strength, which will be assessed using the handgrip test. In contrast, secondary outcomes will evaluate functional capacity through the Short Physical Performance Battery, the Senior Fitness Test and mobility assessments. With its emphasis on arm movements, the Taekwondo-based intervention is expected to improve upper limb strength and overall functional abilities, supporting active ageing and enhancing participants’ quality of life.